2021
DOI: 10.1186/s10020-021-00329-9
|View full text |Cite
|
Sign up to set email alerts
|

Danshensu inhibits the IL-1β-induced inflammatory response in chondrocytes and osteoarthritis possibly via suppressing NF-κB signaling pathway

Abstract: Purpose Osteoarthritis (OA) is the most common inflammatory disease associated with pain and cartilage destruction. Interleukin (IL)-1β is widely used to induce inflammatory response in OA models. This study aimed to explore the role of Danshensu (DSS) in IL-1β-induced inflammatory responses in OA. Methods IL-1β was used to induce chondrocyte inflammation. Cell viability was evaluated by Cell Counting Kit-8 (CCK-8) assay. IL-6, COX-2, TNF-α, and iN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…The cAMP decrease blocked the activation of PKA, leading to the failure of activation of NF-κB [35]. Several studies showed that in OA joint, the activation of NF-κB is one of the main altered pathways causing the onset and progression of this pathology [12,36,37]. Thus, agents activating pathways able to inhibit NF-κB, can be considered suitable pharmacological strategies to treat OA.…”
Section: Discussionmentioning
confidence: 99%
“…The cAMP decrease blocked the activation of PKA, leading to the failure of activation of NF-κB [35]. Several studies showed that in OA joint, the activation of NF-κB is one of the main altered pathways causing the onset and progression of this pathology [12,36,37]. Thus, agents activating pathways able to inhibit NF-κB, can be considered suitable pharmacological strategies to treat OA.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-1β (IL-1β) can induce cartilage degradation by promoting the expression of matrix metalloproteinases (MMPs) in chondrocytes ( 32 ) and is widely used in the inflammatory induction model of chondrocytes in osteoarthritis ( 33 ) . We used IL-1β to stimulate chondrocytes of normal and osteoarthritis person to simulate this microenvironment of inflammation and used qRT-PCR to verify the expression level of hub genes.…”
Section: Methodsmentioning
confidence: 99%
“…Anti-inflammatory effects of the algal sulfated polysaccharides were related to their sulfated content and proportion of monosaccharides. Previous reports suggested that the polysaccharides contain high amounts of the sulfate group, fucose, and galactose, which could inhibit the LPS-induced inflammatory response in RAW 264.7 cells [23][24][25][26][27]. CFCE-PS contains 21.06% sulfate and 70.19% galactose, and significantly inhibited the production of the inflammatory molecules in LPS-stimulated RAW 264.7 cells.…”
Section: Resultsmentioning
confidence: 94%